High-strength composite hammer head and manufacturing process thereof
By using composite materials of high chromium cast iron and medium carbon steel, combined with the use of incubation agent and interface combination additives, as well as high-temperature heat treatment technology, the problems of material performance differences and interface control difficulties in composite hammer manufacturing processes are solved, and high-strength and wear resistance are improved.
Patent Information
- Application Number
- CN202411727317.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the existing composite hammer manufacturing process, the physical, chemical and mechanical properties of bimetallic liquid have large differences, resulting in complex process steps, difficult interface control, metallurgical defects, affecting the mechanical properties and wear resistance.
The composite material of high chromium cast iron and medium carbon steel is used to carry out high-temperature heat treatment through the use of incubation agent and interface combination additive, including low-temperature primary quenching and high-temperature secondary quenching, combined with tempering treatment, forming a fine structure and an optimized interface combination.
It significantly improves the strength and wear resistance of the hammer head material, improves the interface bonding strength, reduces breakage or falloff, and improves the overall efficiency of the composite hammer head.
Smart Images

Figure CN119530640A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and more particularly to a high-strength composite hammer head and a manufacturing process thereof. Background Art
[0002] According to the actual use of the hammer head, different parts are usually required to have different mechanical properties. The hammer handle is required to have certain strength and toughness, while the hammer head is in direct contact with the material, and the end of the hammer is seriously worn, so the end is required to have strong wear resistance. The hammer head cast by traditional single material is costly, consumes a lot, and the strength, toughness and wear resistance are difficult to meet the actual needs. Therefore, in order to meet the use requirements as much as possible, multiple metals are usually cast into composite hammer head castings through composite casting process.
[0003] The main types of composite casting processes include liquid metal infiltration casting, centrifugal composite casting, bimetallic casting, etc. Among them, the bimetallic liquid-liquid composite casting process in bimetallic casting refers to the simultaneous melting of two metals, pouring the two metal liquids into the mold according to the set pouring temperature, and generating metallurgical composites around the interface after cooling. However, in the process of preparing the composite hammer head using the bimetallic liquid-liquid composite casting process, the materials of the bimetallic liquids usually have large differences in physical, chemical and mechanical properties, resulting in high complexity of the process steps for composite casting of the bimetallic liquids to form the composite hammer head, difficulty in interface control, metallurgical defects, etc. It is difficult to accurately control the parameters such as composite casting and heat treatment of the two metal liquids, resulting in uneven distribution of intermetallic compounds or poor interface bonding of the bonding layer at the bonding interface where the two different metal liquids are in contact, affecting the mechanical properties and wear resistance of the composite hammer head and reducing the manufacturing quality of the composite hammer head. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a high-strength composite hammer head and a manufacturing process thereof.
[0005] A high-strength composite hammer head, consisting of a hammer head part and a hammer handle part;
[0006] The chemical composition and mass fraction of the hammer head are: C: 3.0-3.8%, Si: 0.5-1.4%, Mn: 0.5-1.0%, Cr: 18.0-24.0%, Ni: 0.08-0.27%, Al: 0.08-0.19%, Ti: 0.01-0.06%, B: 0.01-0.03% and the balance of Fe and unavoidable impurity elements;
[0007] The chemical composition and mass fraction of the hammer handle are: C: 0.2-0.6%, Si: 0.1-0.8%, Mn: 0.3-1.2%, Cr: 1.1-1.8%, Ni: 0.1-0.65%, Mo: 0.3-0.6% and the remainder of Fe and unavoidable impurity elements.
[0008] A manufacturing process of a high-strength composite hammer head comprises the following steps:
[0009] S1: Melting of hammer material: proportioning according to the requirements of the chemical composition of the hammer part (except Al, Ti, and B), weighing the required hammer material, heating and melting the required hammer material to obtain a high-chromium cast iron melt, adding a slag remover and an inoculating and modifying agent, and performing inoculating and modifying, heat-insulating and standing, and slag removal to obtain a melt for the hammer;
[0010] The inoculating modifier is prepared by mixing AlTiB alloy and chromium nitride in a weight ratio of 1:(0.1-1), and the chemical composition and mass fraction of the AlTiB alloy are: Ti: 4.8-8.2%, B: 1.0-2.3% and the balance of Al and inevitable impurity elements;
[0011] S2: Melting of hammer handle materials: weighing the required hammer handle materials according to the chemical composition requirements of the hammer handle part, heating and melting the required hammer handle materials to obtain medium carbon steel melt, and then heat-insulating, standing and removing slag to obtain a melt for the hammer handle;
[0012] S3: composite casting molding, first pouring the melt for the hammer handle into the bottom of the hammer head model in the sand box, adding an interface bonding agent on the surface of the melt for the hammer handle in the hammer head model, and after the melt for the hammer handle in the hammer head model is naturally cooled and solidified for a period of time, pouring the melt for the hammer head into the hammer head model until the riser on the sand box is filled with the melt for the hammer head, and then stopping the pouring, removing the mixture of the melt for the hammer head and the interface bonding agent at the riser, and keeping the temperature under negative pressure for a period of time, taking it out of the box, and air cooling it to obtain a composite hammer head casting;
[0013] S4: heat treatment processing, after sand cleaning and grinding the composite hammer casting, the composite hammer casting is heated to 630-650°C, kept warm for 50-70 minutes, and then continuously heated to 1030-1050°C, kept warm for 3-4 hours, then the composite hammer casting is air-cooled to 600-620°C, and then air-cooled to room temperature to complete the quenching treatment, kept warm at 430-450°C for 4-5 hours, and the quenched composite hammer casting is tempered. After the tempering is completed, it is air-cooled to room temperature to obtain a high-strength composite hammer.
[0014] Furthermore, the hammer head material includes common scrap steel, carburizer, ferrochrome, ferrosilicon, ferromanganese, and nickel plate.
[0015] Furthermore, the hammer handle material includes common scrap steel, ferrochrome, ferrosilicon, ferromanganese, nickel plate, and ferromolybdenum.
[0016] Further, step S1: smelting hammer material, specifically includes the following steps:
[0017] S1.1: According to the requirements of the chemical composition of the hammer material (except Al, Ti, and B), the required hammer material is weighed and added into the medium frequency induction furnace smelting A, the medium frequency induction furnace smelting A is evacuated to below 150Pa, and argon is introduced into the medium frequency induction furnace smelting A, and smelting is carried out at 1480-1620°C for 30-60min to obtain a high chromium cast iron melt;
[0018] S1.2: adding a slag remover to the high chromium cast iron melt, wherein the weight ratio of the high chromium cast iron melt to the slag remover is 1:(0.001-0.005), and refining the high chromium cast iron melt for 5-10 minutes;
[0019] S1.3: Add inoculant to ladle A, and quickly inject the refined high chromium cast iron melt into ladle A by injection method. The weight ratio of high chromium cast iron melt to inoculant in ladle A is 1:(0.004-0.01). Keep it at 1420-1520℃ for 20-40min, remove the slag, and obtain the melt for hammer.
[0020] Furthermore, the slag remover is at least one of sodium chloride, potassium chloride, calcium fluoride, aluminum chloride or aluminum oxide.
[0021] Further, step S2: smelting the hammer handle material, specifically includes the following steps:
[0022] S2.1: According to the requirements of the chemical composition of the hammer handle part, the required hammer handle material is weighed and added to the medium frequency induction furnace smelting B. The medium frequency induction furnace smelting B is evacuated to below 150Pa, and argon is introduced into the medium frequency induction furnace smelting B. The smelting is carried out at 1560-1620°C for 30-60min to obtain a medium carbon steel melt;
[0023] S2.2: adding a slag remover to the medium carbon steel melt, wherein the weight ratio of the medium carbon steel melt to the slag remover is 1:(0.001-0.005), and refining the medium carbon steel melt for 5-10 minutes;
[0024] S2.3: Pour the refined medium carbon steel melt into ladle B, keep it at 1570-1620℃ for 20-60min, remove the slag, and obtain the melt for hammer handle.
[0025] Further, step S3: composite casting molding, specifically includes the following steps:
[0026] S3.1: Place the hammer head model upside down in the sand box, pour the hammer handle melt into the bottom of the hammer head model within 8 to 15 seconds, and the pouring temperature is 1570 to 1600°C. Then, add an interface bonding additive to the surface of the hammer handle melt in the hammer head model, and the amount of the interface bonding additive added is 0.1 to 0.8% of the mass of the hammer handle melt in the hammer head model;
[0027] S3.2 After the molten hammer handle in the hammer head model is naturally cooled and solidified for 120 to 180 seconds, the molten hammer head is poured into the hammer head model from the riser of the sand box within 10 to 15 seconds until the riser is filled with the molten hammer head. The pouring temperature is 1440 to 1460°C. Since the interface bonding additive has a small specific gravity and a small density, the molten hammer head at the riser contains the floating interface bonding additive. The mixture of the molten hammer head and the interface bonding additive at the riser is removed to complete the pouring;
[0028] S3.3 After the pouring is completed, the casting is kept warm for 6 to 8 hours under a negative pressure of 0.03 to 0.05 MPa, and the obtained casting is taken out of the box and placed in the air to cool to obtain a composite hammer head casting.
[0029] Furthermore, the interface bonding aid is prepared by mixing graphite powder and sodium borate in a weight ratio of 1: (0.5-1.5).
[0030] Further, step S4: heat treatment processing, specifically comprising the following steps:
[0031] S4.1: The composite hammer casting is sanded and polished, and then the polished composite hammer casting is placed in a heating furnace, heated to 630-650°C at a heating rate of 60-70°C / h, and kept warm for 50-70 min, and then continuously heated to 1030-1050°C at a heating rate of 10-20°C / min, and kept warm for 3-4 h;
[0032] S4.2: Then, the composite hammer casting is taken out from the heating furnace, air-cooled to 600-620°C, and then air-cooled to room temperature to complete the quenching treatment;
[0033] S4.3: Place the quenched composite hammer casting into a heating furnace heated to 430-450°C and keep it at this temperature for 4-5 hours for tempering treatment;
[0034] S4.4: After tempering, air cool to room temperature, take out the tempered composite hammer casting from the heating furnace, and obtain a high-strength composite hammer.
[0035] The present invention has the following advantages:
[0036] 1. In the present invention, the inoculating modifier has a common effect of modification and refinement on the high chromium cast iron melt. Under the synergistic effect of chromium nitride and AlTiB alloy, the formed AlCr, TiB2, TiC and other compounds can serve as heterogeneous nucleation cores in the solidification process of high chromium cast iron at high temperature, promote the refinement of grains and carbides, hinder the growth of carbides, achieve significant grain refinement effect, form a fine organizational structure, and help improve the strength and wear resistance of the hammer material.
[0037] 2. In the present invention, a composite hammer head casting is obtained by casting a hammer handle melt and a hammer head melt. During the casting process, after the hammer handle melt is poured into the hammer head mold to form a hammer handle part, an interface bonding agent is added to cover the surface layer of the hammer handle melt with a layer of interface bonding agent. The sodium borate component in the interface bonding agent has the characteristics of low melting point, low density, low viscosity and low surface tension, and can provide good lubricity to the surface layer of the hammer handle melt, which is beneficial to reduce the formation of oxides and improve the cleanliness of the surface of the hammer handle melt. The graphite powder component in the interface bonding agent can effectively reduce the oxides formed on the surface of the hammer handle melt, generate gas insoluble in the metal liquid, and discharge it out of the hammer head mold, effectively ensuring the metallurgical diffusion bonding of the hammer head melt with the hammer handle melt after the subsequent hammer head melt is poured into the hammer head mold, thereby improving the interface bonding strength of the composite hammer head casting, reducing the breakage or shedding at the interface, and improving the overall performance of the composite hammer head.
[0038] 3. In the process of heat treatment of the composite hammer casting of the present invention, quenching treatment is first performed and then tempering treatment is performed. In the quenching treatment, the temperature is first raised to 630-650°C at a slow heating rate of 60-70°C / h and kept warm, and low-temperature primary quenching treatment is performed, which can effectively eliminate the internal stress caused by the temperature gradient on the surface and core of the composite hammer casting, thereby reducing the deformation and cracking of the composite hammer. Then, the temperature is continuously raised to 1030-1050°C at a heating rate of 10-20°C / min and kept warm, and high-temperature secondary quenching treatment is performed. The combination of low-temperature secondary quenching treatment can effectively enhance the wear resistance and impact toughness of the high-strength composite hammer. During the tempering treatment, rapid heating and tempering can eliminate the internal stress generated in the composite hammer casting during quenching, so that the handle part of the high-strength composite hammer is composed of bainite and tempered troostite, and the hammer part is composed of long martensite, ledeburite and a small amount of pearlite. The long martensite in the hammer part can serve as a matrix to provide support for the carbides in the hammer part, so that the carbides are scattered in a strip shape, effectively improving the hardness and wear resistance of the high-strength composite hammer. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flowchart of a manufacturing process of a high-strength composite hammer head used in an embodiment of the present invention.
[0040] Figure 2 This is a diagram showing the microhardness variation of the interface transition region of the high-strength composite hammer head of the embodiment of the present invention and comparative example 4. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] A manufacturing process for a high-strength composite hammer head, such as Figure 1 As shown, the specific steps include:
[0044] S1: Hammer material smelting,
[0045] S1.1: According to the following chemical composition and mass fraction: C: 3.2%, Si: 0.8%, Mn: 0.8%, Cr: 21.0%, Ni: 0.15% and the balance of Fe and unavoidable impurity elements, weigh the required ordinary scrap steel, carburizer, ferrochrome, ferrosilicon, ferromanganese and nickel plate as hammer materials, add the hammer materials into medium frequency induction furnace smelting A, evacuate the medium frequency induction furnace smelting A to below 150Pa, and introduce argon gas into the medium frequency induction furnace smelting A, smelt at 1620°C for 60min to obtain a high chromium cast iron melt;
[0046] S1.2: adding potassium chloride to the high chromium cast iron melt, the weight ratio of the high chromium cast iron melt to potassium chloride is 1:0.005, and refining the high chromium cast iron melt for 10 minutes;
[0047] S1.3: adding an inoculant to ladle A, and quickly pouring the refined high chromium cast iron melt into ladle A, wherein the weight ratio of the high chromium cast iron melt to the inoculant in ladle A is 1:0.01, and the mixture is kept at 1520°C for 40 minutes, and the slag is removed to obtain a melt for the hammer head;
[0048] The preparation steps of the inoculant modifier are as follows: adding AlTiB alloy to a crusher, crushing the AlTiB alloy into particles with a particle size of 3 mm to obtain alloy particles, stirring and mixing the alloy particles with chromium nitride powder in a weight ratio of 1:0.8 to obtain the inoculant modifier, wherein the chemical composition and mass fraction of the AlTiB alloy are: Ti: 6.5%, B: 1.8% and the balance of Al and unavoidable impurity elements;
[0049] S2: Hammer handle material smelting,
[0050] S2.1: According to the requirements of the chemical composition of the hammer handle part, the chemical composition and mass fraction of the hammer handle part are: C: 0.6%, Si: 0.3%, Mn: 0.8%, Cr: 1.3%, Ni: 0.15%, Mo: 0.5% and the remaining Fe and unavoidable impurity elements, weigh the required ordinary scrap steel, ferrochrome, ferrosilicon, ferromanganese, nickel plate and ferromolybdenum as the hammer handle material, add the hammer handle material into the medium frequency induction furnace smelting B, the medium frequency induction furnace smelting B is evacuated to below 150Pa, and argon is introduced into the medium frequency induction furnace smelting B, and smelting is carried out at 1620℃ for 60min to obtain a medium carbon steel melt;
[0051] S2.2: adding potassium chloride to the medium carbon steel melt, the weight ratio of the medium carbon steel melt to potassium chloride is 1:0.005, and refining the medium carbon steel melt for 10 minutes;
[0052] S2.3: Pour the refined medium carbon steel melt into ladle B, keep it at 1620°C for 60 minutes, remove the slag, and obtain the melt for hammer handle;
[0053] S3: Composite casting,
[0054] S3.1: The hammer head model in the sand box is in an inverted state, and the hammer handle melt is poured into the bottom of the hammer head model within 15 seconds, and the pouring temperature is 1600°C. Subsequently, an interface bonding agent is added to the surface of the hammer handle melt in the hammer head model to prevent oxidation of the surface of the hammer handle melt in the hammer head model. The amount of the interface bonding agent added is 0.3% of the mass of the hammer handle melt in the hammer head model. The interface bonding agent is prepared by mixing graphite powder and sodium borate in a weight ratio of 1:1;
[0055] S3.2 After the molten hammer handle in the hammer head model is naturally cooled and solidified for 180 seconds, the molten hammer head is poured into the hammer head model from the riser of the sand box within 15 seconds until the riser is filled with the molten hammer head. The pouring temperature is 1460°C. Since the interface bonding additive has a small specific gravity and a small density, the molten hammer head at the riser contains the interface bonding additive added to the hammer head model and floated. Then, the mixture of the molten hammer head and the interface bonding additive at the riser is removed to complete the pouring;
[0056] S3.3 After the pouring is completed, the casting is kept warm for 8 hours under a negative pressure of 0.05 MPa, and the obtained casting is taken out of the box and placed in the air for cooling to obtain a composite hammer head casting;
[0057] S4: Heat treatment processing,
[0058] S4.1: The composite hammer casting is sanded and polished, and then the polished composite hammer casting is placed in a heating furnace, heated to 650°C at a rate of 60°C / h, and kept warm for 60 min. Then, the temperature is continuously raised to 1050°C at a heating rate of 20°C / min, and kept warm for 4 h.
[0059] S4.2: Then, the composite hammer casting is taken out from the heating furnace, air-cooled to 620°C, and then air-cooled to room temperature to complete the quenching treatment;
[0060] S4.3: Place the quenched composite hammer casting in a heating furnace heated to 450°C and keep it at this temperature for 5 hours for tempering treatment to eliminate the internal stress generated during quenching;
[0061] S4.4: After tempering, air cool to room temperature, take out the tempered composite hammer casting from the heating furnace, and obtain a high-strength composite hammer.
[0062] Example 2
[0063] A manufacturing process for a high-strength composite hammer head, such as Figure 1 As shown, the specific steps include:
[0064] S1: Hammer material smelting,
[0065] S1.1: According to the following chemical composition and mass fraction: C: 3.2%, Si: 0.8%, Mn: 0.8%, Cr: 21.0%, Ni: 0.15% and the balance of Fe and unavoidable impurity elements, weigh the required ordinary scrap steel, carburizer, ferrochrome, ferrosilicon, ferromanganese and nickel plate as hammer materials, add the hammer materials into medium frequency induction furnace smelting A, evacuate the medium frequency induction furnace smelting A to below 150Pa, and introduce argon gas into the medium frequency induction furnace smelting A, smelt at 1540°C for 30min to obtain a high chromium cast iron melt;
[0066] S1.2: adding potassium chloride to the high chromium cast iron melt, the weight ratio of the high chromium cast iron melt to potassium chloride is 1:0.005, and refining the high chromium cast iron melt for 5 minutes;
[0067] S1.3: adding an inoculant to ladle A, and quickly pouring the refined high chromium cast iron melt into ladle A, wherein the weight ratio of the high chromium cast iron melt to the inoculant in ladle A is 1:0.01, and the mixture is kept at 1420°C for 20 minutes, and the slag is removed to obtain a melt for the hammer head;
[0068] The preparation steps of the inoculant modifier are as follows: adding AlTiB alloy to a crusher, crushing the AlTiB alloy into particles with a particle size of 3 mm to obtain alloy particles, stirring and mixing the alloy particles with chromium nitride powder in a weight ratio of 1:0.8 to obtain the inoculant modifier, wherein the chemical composition and mass fraction of the AlTiB alloy are: Ti: 6.5%, B: 1.8% and the balance of Al and unavoidable impurity elements;
[0069] S2: Hammer handle material smelting,
[0070] S2.1: According to the requirements of the chemical composition of the hammer handle part, the chemical composition and mass fraction of the hammer handle part are: C: 0.6%, Si: 0.3%, Mn: 0.8%, Cr: 1.3%, Ni: 0.15%, Mo: 0.5% and the remaining Fe and unavoidable impurity elements, weigh the required ordinary scrap steel, ferrochrome, ferrosilicon, ferromanganese, nickel plate and ferromolybdenum as the hammer handle material, add the hammer handle material into the medium frequency induction furnace smelting B, the medium frequency induction furnace smelting B is evacuated to below 150Pa, and argon is introduced into the medium frequency induction furnace smelting B, and smelting is carried out at 1560℃ for 30min to obtain a medium carbon steel melt;
[0071] S2.2: adding potassium chloride to the medium carbon steel melt, the weight ratio of the medium carbon steel melt to potassium chloride is 1:0.005, and refining the medium carbon steel melt for 5 minutes;
[0072] S2.3: Pour the refined medium carbon steel melt into ladle B, keep it at 1570°C for 20 min, remove the slag, and obtain the melt for hammer handle;
[0073] S3: Composite casting,
[0074] S3.1: The hammer head model in the sand box is in an inverted state, and the hammer handle melt is poured into the bottom of the hammer head model within 8 seconds, and the pouring temperature is 1570°C. Subsequently, an interface bonding agent is added to the surface of the hammer handle melt in the hammer head model to prevent oxidation of the surface of the hammer handle melt in the hammer head model. The amount of the interface bonding agent added is 0.3% of the mass of the hammer handle melt in the hammer head model. The interface bonding agent is prepared by mixing graphite powder and sodium borate in a weight ratio of 1:1;
[0075] S3.2 After the molten hammer handle in the hammer head model is naturally cooled and solidified for 120 seconds, the molten hammer head is poured into the hammer head model from the riser of the sand box within 10 seconds, and the pouring is stopped when the riser is filled with the molten hammer head. The pouring temperature is 1440°C. Since the interface bonding additive has a small specific gravity and a small density, the molten hammer head at the riser contains the interface bonding additive added to the hammer head model and floated. Then, the mixture of the molten hammer head and the interface bonding additive at the riser is removed to complete the pouring;
[0076] S3.3 After the pouring is completed, the casting is kept warm for 6 hours under a negative pressure of 0.03 MPa, and the obtained casting is taken out of the box and placed in the air for cooling to obtain a composite hammer head casting;
[0077] S4: Heat treatment processing,
[0078] S4.1: The composite hammer casting is sanded and polished, and then the polished composite hammer casting is placed in a heating furnace, heated to 630°C at a rate of 70°C / h, and kept warm for 50 min. Then, the temperature is continuously raised to 1030°C at a heating rate of 10°C / min, and kept warm for 3 h.
[0079] S4.2: Then, the composite hammer head casting is taken out from the heating furnace, air-cooled to 600°C, and then air-cooled to room temperature to complete the quenching treatment;
[0080] S4.3: Place the quenched composite hammer casting in a heating furnace heated to 430°C and keep it at this temperature for 4 hours for tempering to eliminate the internal stress generated during quenching;
[0081] S4.4: After tempering, air cool to room temperature, take out the tempered composite hammer casting from the heating furnace, and obtain a high-strength composite hammer.
[0082] Example 3
[0083] A manufacturing process for a high-strength composite hammer head, such as Figure 1 As shown, the specific steps include:
[0084] S1: Hammer material smelting,
[0085] S1.1: According to the following chemical composition and mass fraction: C: 3.6%, Si: 1.2%, Mn: 0.5%, Cr: 18.0%, Ni: 0.1% and the balance of Fe and unavoidable impurity elements, weigh the required ordinary scrap steel, carburizer, ferrochrome, ferrosilicon, ferromanganese and nickel plate as hammer materials, add the hammer materials into medium frequency induction furnace smelting A, evacuate the medium frequency induction furnace smelting A to below 150Pa, and introduce argon gas into the medium frequency induction furnace smelting A, smelt at 1620°C for 60min to obtain a high chromium cast iron melt;
[0086] S1.2: adding potassium chloride to the high chromium cast iron melt, the weight ratio of the high chromium cast iron melt to potassium chloride is 1:0.002, and refining the high chromium cast iron melt for 10 minutes;
[0087] S1.3: Add inoculant to ladle A, and quickly pour the refined high chromium cast iron melt into ladle A. The weight ratio of high chromium cast iron melt to inoculant in ladle A is 1:0.004. Keep the mixture at 1520°C for 40 minutes, remove the slag, and obtain the melt for hammer head.
[0088] The preparation steps of the inoculant modifier are as follows: adding AlTiB alloy to a crusher, crushing the AlTiB alloy into particles with a particle size of 3 mm to obtain alloy particles, stirring and mixing the alloy particles with chromium nitride powder in a weight ratio of 1:1 to obtain the inoculant modifier, wherein the chemical composition and mass fraction of the AlTiB alloy are: Ti: 4.8%, B: 1.4% and the balance of Al and unavoidable impurity elements;
[0089] S2: Hammer handle material smelting,
[0090] S2.1: According to the requirements of the chemical composition of the hammer handle part, the proportioning is carried out, and the chemical composition and mass fraction of the hammer handle part are: C: 0.3%, Si: 0.5%, Mn: 1.1%, Cr: 1.5%, Ni: 0.33%, Mo: 0.3% and the remaining Fe and inevitable impurity elements, and the required ordinary scrap steel, ferrochrome, ferrosilicon, ferromanganese, nickel plate and ferromolybdenum are weighed as the hammer handle material, and the hammer handle material is added into the medium frequency induction furnace smelting B, and the medium frequency induction furnace smelting B is evacuated to below 150Pa, and argon gas is introduced into the medium frequency induction furnace smelting B, and smelting is carried out at 1620℃ for 60min to obtain a medium carbon steel melt;
[0091] S2.2: adding potassium chloride to the medium carbon steel melt, the weight ratio of the medium carbon steel melt to potassium chloride is 1:0.002, and refining the medium carbon steel melt for 10 minutes;
[0092] S2.3: Pour the refined medium carbon steel melt into ladle B, keep it at 1620°C for 60 minutes, remove the slag, and obtain the melt for hammer handle;
[0093] S3: Composite casting,
[0094] S3.1: The hammer head model in the sand box is in an inverted state, and the hammer handle melt is poured into the bottom of the hammer head model within 15 seconds, and the pouring temperature is 1600°C. Subsequently, an interface bonding agent is added to the surface of the hammer handle melt in the hammer head model to play an anti-oxidation protection role on the surface of the hammer handle melt in the hammer head model. The amount of the interface bonding agent added is 0.6% of the mass of the hammer handle melt in the hammer head model. The interface bonding agent is prepared by mixing graphite powder and sodium borate in a weight ratio of 1:0.5;
[0095] S3.2 After the molten hammer handle in the hammer head model is naturally cooled and solidified for 180 seconds, the molten hammer head is poured into the hammer head model from the riser of the sand box within 15 seconds until the riser is filled with the molten hammer head. The pouring temperature is 1460°C. Since the interface bonding additive has a small specific gravity and a small density, the molten hammer head at the riser contains the interface bonding additive added to the hammer head model and floated. Then, the mixture of the molten hammer head and the interface bonding additive at the riser is removed to complete the pouring;
[0096] S3.3 After the pouring is completed, the casting is kept warm for 8 hours under a negative pressure of 0.05 MPa, and the obtained casting is taken out of the box and placed in the air for cooling to obtain a composite hammer head casting;
[0097] S4: Heat treatment processing,
[0098] S4.1: The composite hammer casting is sanded and polished, and then the polished composite hammer casting is placed in a heating furnace, heated to 650°C at a rate of 60°C / h, and kept warm for 60 min. Then, the temperature is continuously raised to 1050°C at a heating rate of 20°C / min, and kept warm for 4 h.
[0099] S4.2: Then, the composite hammer casting is taken out from the heating furnace, air-cooled to 620°C, and then air-cooled to room temperature to complete the quenching treatment;
[0100] S4.3: Place the quenched composite hammer casting in a heating furnace heated to 450°C and keep it at this temperature for 5 hours for tempering treatment to eliminate the internal stress generated during quenching;
[0101] S4.4: After tempering, air cool to room temperature, take out the tempered composite hammer casting from the heating furnace, and obtain a high-strength composite hammer.
[0102] Comparative Example 1
[0103] Compared with Example 1, the difference of Comparative Example 1 is that the operation of adding the inoculant in step S1.3 is removed. After the refining is completed, the refined high chromium cast iron melt is directly poured into ladle A, kept at 1520°C for 40 minutes, slag is removed, and the melt for the hammer is obtained. The other steps remain unchanged to prepare a high-strength composite hammer, which is recorded as Comparative Example 1.
[0104] Comparative Example 2
[0105] Compared with Example 1, the difference of Comparative Example 2 is that the inoculating modifier in step S1.3 is composed only of chromium nitride, and the other steps remain unchanged to prepare a high-strength composite hammer head, which is recorded as Comparative Example 2.
[0106] Comparative Example 3
[0107] Compared with Example 1, the difference of Comparative Example 3 is that the inoculating modifier in step S1.3 is composed only of AlTiB alloy, and the other steps remain unchanged to prepare a high-strength composite hammer head, which is recorded as Comparative Example 3.
[0108] Comparative Example 4
[0109] Compared with Example 1, the difference of Comparative Example 4 is that the step of adding the interface bonding agent in step S3.1 is removed, and after the melt of the hammer handle is injected into the hammer head mold, the melt of the hammer handle part in the hammer head mold is directly allowed to naturally cool and solidify, and the other steps remain unchanged to prepare a high-strength composite hammer head, which is recorded as Comparative Example 4.
[0110] Comparative Example 5
[0111] Compared with Example 1, the difference of Comparative Example 5 is that, in step S4.1, after the polished composite hammer head casting is placed in the heating furnace, the temperature is directly increased to 1050°C at a heating rate of 20°C / min and kept warm for 4 hours. The other steps remain unchanged to prepare a high-strength composite hammer head, which is recorded as Comparative Example 5.
[0112] Comparative Example 6
[0113] Compared with Example 1, the difference of Comparative Example 6 is that steps S4.3-S4.4 are removed, and after the quenching treatment is completed, a high-strength composite hammer head is obtained, and the remaining steps remain unchanged, which is recorded as Comparative Example 6.
[0114] Wear resistance test
[0115] According to the national standard GB / T12444-2006, the friction and wear performance of the hammer head of the high-strength composite hammer head in Examples 1-3 and Comparative Examples 1-6 was tested using an M-2000 abrasive wear tester, with a load of 200N, a test time of 2h, and a speed of 200rad / min. The weight of the high-strength composite hammer head before and after wear was weighed and recorded, and the wear rate was calculated. The wear rate calculation formula is: S0 and S1 are the weights of the high-strength composite hammer head before and after wear. The test results of wear resistance are shown in Table 1.
[0116] Table 1:
[0117] Group Wear rate (%) Example 1 0.76 Example 2 0.91 Example 3 0.88 Comparative Example 1 1.67 Comparative Example 2 1.26 Comparative Example 3 1.51 Comparative Example 4 1.05 Comparative Example 5 1.82 Comparative Example 6 1.59
[0118] As shown in Table 1, after the wear test, the wear rate of the high-strength composite hammer heads of Examples 1-3 is less than 1%, and the wear results are better than those of Comparative Examples 1-6, and have good wear resistance. It is explained that in the process of smelting the hammer head material, the wear resistance of the hammer head material can be effectively improved by inoculating and modifying the hammer head melt with an inoculating modifier prepared by mixing AlTiB alloy and chromium nitride. The AlTiB alloy and chromium nitride in the inoculating modifier cooperate with each other during the inoculating and modifying process, which can promote the refinement of grains and carbides in the hammer head melt and form a fine structure; and in the heat treatment process of the composite hammer head casting, before high-temperature quenching, the high-low temperature secondary quenching process of heating to 630-650℃ at a slow heating rate of 60-70℃ / h for low-temperature quenching and the tempering treatment can have a significant effect on the wear resistance of the high-strength composite hammer head.
[0119] Mechanical properties test
[0120] According to the national standard GB / T3808-2002, the high-strength composite hammer heads in Examples 1-3 and Comparative Examples 1-6 were tested for impact strength using a pendulum impact tester; according to the standard GB / T24186-2009, the high-strength composite hammer heads in Examples 1-3 and Comparative Examples 1-6 were tested for tensile strength and hardness. The test results of mechanical properties are shown in Table 2.
[0121] Table 2:
[0122]
[0123] As can be seen from Table 2, the impact toughness, tensile strength and hardness of the hammer head part and the hammer handle part of the high-strength composite hammer head of Examples 1-3 are better than those of the high-strength composite hammer head of Comparative Examples 1-5, indicating that in the preparation process of the high-strength composite hammer head, the inoculation and modification treatment of the inoculating and modifying agent, the addition and use of the interface bonding additive and the heat treatment processing technology within a specific temperature range can all play an effect of improving the hardness and toughness of the high-strength composite hammer head, which is beneficial to enhancing the mechanical properties of the high-strength composite hammer head.
[0124] Interface binding assay
[0125] The interface transition area of the high-strength composite hammer heads of Examples 1-3 and Comparative Example 4 was sampled by wire cutting, and processed into block samples. The microhardness of the block samples at different positions was measured by a microhardness tester. Five points were measured at each position, and the average value was taken as the test result. The results are shown in FIG. Figure 2 shown.
[0126] like Figure 2It can be seen that the microhardness of the interface of the high-strength composite hammer head in Examples 1-3 is greater, and the microhardness transition in the interface transition area is more gentle and uniform, indicating that the addition of the interface bonding additive not only improves the hardness of the high-strength composite hammer head, especially the hardness of the hammer handle part, but also helps to alleviate the hardness change in the transition area between the hammer head part and the hammer handle part, thereby enhancing the high-strength composite hammer head.
[0127] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A high-strength composite hammer head, characterized in that: It consists of a hammer head and a hammer handle: The chemical composition and mass fraction of the hammer head are: C: 3.0-3.8%, Si: 0.5-1.4%, Mn: 0.5-1.0%, Cr: 18.0-24.0%, Ni: 0.08-0.27%, Al: 0.08-0.19%, Ti: 0.01-0.06%, B: 0.01-0.03% and the balance of Fe and unavoidable impurity elements; The chemical composition and mass fraction of the hammer handle are: C: 0.2-0.6%, Si: 0.1-0.8%, Mn: 0.3-1.2%, Cr: 1.1-1.8%, Ni: 0.1-0.65%, Mo: 0.3-0.6% and the remainder of Fe and unavoidable impurity elements.
2. The manufacturing process of a high-strength composite hammer head according to claim 1, characterized in that: The following steps are involved: S1: Melting of hammer material: proportioning according to the requirements of the chemical composition of the hammer part (except Al, Ti, and B), weighing the required hammer material, heating and melting the required hammer material to obtain a high-chromium cast iron melt, adding a slag remover and an inoculating and modifying agent, and performing inoculating and modifying, heat-insulating and standing, and slag removal to obtain a melt for the hammer; The inoculating modifier is prepared by mixing AlTiB alloy and chromium nitride in a weight ratio of 1:(0.1-1), and the chemical composition and mass fraction of the AlTiB alloy are: Ti: 4.8-8.2%, B: 1.0-2.3% and the balance of Al and inevitable impurity elements; S2: Melting of hammer handle materials: weighing the required hammer handle materials according to the chemical composition requirements of the hammer handle part, heating and melting the required hammer handle materials to obtain medium carbon steel melt, and then heat-insulating, standing and removing slag to obtain a melt for the hammer handle; S3: composite casting molding, first pouring the melt for the hammer handle into the bottom of the hammer head model in the sand box, adding an interface bonding agent on the surface of the melt for the hammer handle in the hammer head model, and after the melt for the hammer handle in the hammer head model is naturally cooled and solidified for a period of time, pouring the melt for the hammer head into the hammer head model until the riser on the sand box is filled with the melt for the hammer head, and then stopping the pouring, removing the mixture of the melt for the hammer head and the interface bonding agent at the riser, and keeping the temperature under negative pressure for a period of time, taking it out of the box, and air cooling it to obtain a composite hammer head casting; S4: heat treatment processing, after sand cleaning and grinding the composite hammer casting, the composite hammer casting is heated to 630-650°C, kept warm for 50-70 minutes, and then continuously heated to 1030-1050°C, kept warm for 3-4 hours, then the composite hammer casting is air-cooled to 600-620°C, and then air-cooled to room temperature to complete the quenching treatment, kept warm at 430-450°C for 4-5 hours, and the quenched composite hammer casting is tempered. After the tempering is completed, it is air-cooled to room temperature to obtain a high-strength composite hammer.
3. The manufacturing process of a high-strength composite hammer head according to claim 2, characterized in that: Hammer head materials include ordinary scrap steel, carburizer, ferrochrome, ferrosilicon, ferromanganese and nickel plate.
4. The manufacturing process of a high-strength composite hammer head according to claim 3, characterized in that: The hammer handle materials include ordinary scrap steel, ferrochrome, ferrosilicon, ferromanganese, nickel plate and ferromolybdenum.
5. The manufacturing process of a high-strength composite hammer head according to claim 2, characterized in that: Step S1: Melting of hammer material, specifically including the following steps: S1.1: According to the requirements of the chemical composition of the hammer material (except Al, Ti, and B), the required hammer material is weighed and added into the medium frequency induction furnace smelting A, the medium frequency induction furnace smelting A is evacuated to below 150Pa, and argon is introduced into the medium frequency induction furnace smelting A, and smelting is carried out at 1480-1620°C for 30-60min to obtain a high chromium cast iron melt; S1.2: adding a slag remover to the high chromium cast iron melt, wherein the weight ratio of the high chromium cast iron melt to the slag remover is 1:(0.001-0.005), and refining the high chromium cast iron melt for 5-10 minutes; S1.3: Add inoculant to ladle A, and quickly inject the refined high chromium cast iron melt into ladle A by injection method. The weight ratio of high chromium cast iron melt to inoculant in ladle A is 1:(0.004-0.01). Keep it at 1420-1520℃ for 20-40min, remove the slag, and obtain the melt for hammer.
6. The manufacturing process of a high-strength composite hammer head according to claim 5, characterized in that: The slag remover is at least one of sodium chloride, potassium chloride, calcium fluoride, aluminum chloride or aluminum oxide.
7. The manufacturing process of a high-strength composite hammer head according to claim 2, characterized in that: Step S2: Melting of hammer handle material, specifically including the following steps: S2.1: According to the requirements of the chemical composition of the hammer handle part, the required hammer handle material is weighed and added to the medium frequency induction furnace smelting B. The medium frequency induction furnace smelting B is evacuated to below 150Pa, and argon is introduced into the medium frequency induction furnace smelting B. The smelting is carried out at 1560-1620°C for 30-60min to obtain a medium carbon steel melt; S2.2: adding a slag remover to the medium carbon steel melt, wherein the weight ratio of the medium carbon steel melt to the slag remover is 1:(0.001-0.005), and refining the medium carbon steel melt for 5-10 minutes; S2.3: Pour the refined medium carbon steel melt into ladle B, keep it at 1570-1620℃ for 20-60min, remove the slag, and obtain the melt for hammer handle.
8. The manufacturing process of a high-strength composite hammer head according to claim 2, characterized in that: Step S3: composite casting, specifically comprising the following steps: S3.1: The hammer head model is placed upside down in a sand box, and the melt for the hammer handle is first poured into the bottom of the hammer head model within 8 to 15 seconds, and the pouring temperature is 1570 to 1600°C. Subsequently, an interface bonding additive is added to the surface of the melt for the hammer handle in the hammer head model, and the amount of the interface bonding additive added is 0.1 to 0.8% of the mass of the melt for the hammer handle in the hammer head model; S3.2 After the molten hammer handle in the hammer head model is naturally cooled and solidified for 120 to 180 seconds, the molten hammer head is poured into the hammer head model from the riser of the sand box within 10 to 15 seconds until the riser is filled with the molten hammer head. The pouring temperature is 1440 to 1460°C. Since the interface bonding additive has a small specific gravity and a small density, the molten hammer head at the riser contains the floating interface bonding additive. The mixture of the molten hammer head and the interface bonding additive at the riser is removed to complete the pouring; S3.3 After the pouring is completed, the casting is kept warm for 6 to 8 hours under a negative pressure of 0.03 to 0.05 MPa, and the obtained casting is taken out of the box and placed in the air to cool to obtain a composite hammer head casting.
9. The manufacturing process of a high-strength composite hammer head according to claim 8, characterized in that: The interface bonding aid is prepared by mixing graphite powder and sodium borate in a weight ratio of 1: (0.5-1.5).
10. The manufacturing process of a high-strength composite hammer head according to claim 2, characterized in that: Step S4: heat treatment, specifically including the following steps: S4.1: The composite hammer casting is sanded and polished, and then the polished composite hammer casting is placed in a heating furnace, heated to 630-650°C at a heating rate of 60-70°C / h, and kept warm for 50-70 min, and then continuously heated to 1030-1050°C at a heating rate of 10-20°C / min, and kept warm for 3-4 h; S4.2: Then, the composite hammer casting is taken out from the heating furnace, air-cooled to 600-620°C, and then air-cooled to room temperature to complete the quenching treatment; S4.3: Place the quenched composite hammer casting into a heating furnace heated to 430-450°C and keep it at this temperature for 4-5 hours for tempering treatment; S4.4: After tempering, air cool to room temperature, take out the tempered composite hammer casting from the heating furnace, and obtain a high-strength composite hammer.
Citation Information
Patent Citations
Preparation method of wear-resistant high-chromium cast iron
CN103436773A
Bearing steel and manufacturing process of wear-resistant bearing
CN103602920A
Double-liquid double-metal oil quenching hammer and machining method thereof
CN103667870A
Manufacturing technique for duplex metal compound crusher hammerhead
CN103990777A
Low-cost and high-toughness heterogeneous alloy abrasion-resisting hammerhead and manufacturing method thereof
CN108546883A